Associations among particulate matter, hazardous air pollutants and methane emissions from the Aliso Canyon natural gas storage facility during the 2015 blowout. (November 2019) - Garcia-Gonzales, Diane A.; Popoola, Olalekan; Bright, Vivien B.; Paulson, Suzanne E.; Wang, Yanwen; Jones, Roderic L.; Jerrett, Michael
Abstract: In October of 2015, a large underground storage well at the Aliso Canyon natural gas storage facility experienced a massive methane leak (also referred to as "natural gas blowout"), which resulted in the largest ever anthropogenic release of methane from a single point source in the United States. Additional sampling conducted during the event revealed unique gas and particle concentrations in ambient air and a characteristic "fingerprint" of metals in the indoor dust samples similar to samples taken at the blowout site. We further investigated the association between the Aliso Canyon natural gas storage site and several measured air pollutants by: (a) conducting additional emission source studies using meteorological data and correlations between particulate matter, methane, and hazardous air pollutants (HAPs) collected during the natural gas blowout at distances ranging from 1.2 to 7.3 km due south of well SS25, (b) identifying the unique i / n -pentane ratio signature associated with emissions from the blowout event, and (c) identifying characteristics unique to the homes that tested positive for air pollutants using data collected from extensive indoor environmental assessment surveys. Results of air quality samples collected near Aliso Canyon during the final weeks of the event revealed that elevated levels of several HAP compounds were likely influenced by the active natural gas blowout. Furthermore, the final attempts to plug the well during the days preceding the well kill were associated with particle emissions likely from the well site. Together, this investigation suggests uncontrolled leaks or blowout events at natural gas storage facilities have the potential to release harmful pollutants with adverse health and environmental consequences into proximate communities. With this evidence, our recommendations include facility-specific meteorological and air quality data-collection equipment installed at natural gas storage facilities and support of environmental surveillance after severe off-normal operation events. Graphical abstract: Unlabelled Image Highlights: Evidence suggests that a broad range of hazardous air pollutants (HAPs) were co-emitted during elevated methane emissions. We found evidence that the final well kill attempts were associated with particle emissions likely from the SS25 well site. Accidents at natural gas storage facilities have the potential to release harmful pollutants into proximate communities.